THE USE OF INTERFAOL METHODS IN IMPROVING THE QUALITY OF FINE ARTS LESSONS IN EDUCATIONAL EDUCATION (Academicia Globe: Inderscience Research, 2024)
The article gives examples of the methods tested in their experience of using interactive methods to increase the effectiveness of visual art lessons in educational processes, and introduces the components of these methods, organizational processes.